The Formation of Synergetic Thinking Within the Contemporary Democratic Educational Paradigm: A Philosophical Analysis - Fayziyeva Mutabar Mardonovna (Researchparks Publishing, 2026)
This article analyses the formtion of synergetic thinking within the contemporary democratic educational paradigm. The study proceeds from the idea that democratic education changes not only teaching methods, but also the cognitive culture of learners, especially their logical, reflective and projective modes of thinking. The purpose of the article is to determine how synergetic methodology explains nonlinearity, self-organisation and openness in the educational process, and how these processes are manifested in the national educational context of Uzbekistan. The research is based on comparative philosophical analysis, systems thinking, and inductive-deductive reasoning. The results show that synergetic thinking develops most effectively when democratic principles are harmonised with national moral, cultural and pedagogical values. The article concludes that traditional and democratic educational paradigms should not be treated as mutually exclusive; rather, they function as complementary dimensions of contemporary education.